Perinatal Pyogenic Liver Abscess: A Rare Entity and First Reported Case of Klebsiella pneumoniae - Schmiedecke, Stacey S.; Napolitano, Peter G.; Estrada, Sarah M. (American Journal of Perinatology Reports, 2019)
Introduction Pyogenic liver abscess (PLA) is a rare clinical entity, occurring in ∼2.3 per 100,000 patients. Perinatal PLA syndromes are exceedingly rare with just seven previously described cases in the literature and no prior Klebsiella-associated reports.Case A 29-year-old gravida 2 para 1 woman at 11 weeks gestation reporting fever, body aches, and headache. Search for an infectious source identified a 4-cm liver abscess. Percutaneous drainage confirmed Klebsiella pneumoniae infection. The patient was treated with antibiotics until imaging verified complete resolution of the abscess.Conclusion PLA is an uncommon etiology of sepsis in pregnancy. A thorough workup until a source was identified resulted in accurate diagnosis. This allowed for directed therapy and prompt recovery, undoubtedly contributing to favorable pregnancy outcomes in this first report of Klebsiella-associated perinatal PLA.
Keywords: pyogenic liver abscess; liver abscess; pregnancy; sepsis; perinatal infection